Marine Macro Debris from Makassar Strait Beaches with Three Different Designations. (April 2019) - Isyrini, R; Nafie, Y A La; Ukkas, M; Rachim, R; Cordova, M R
Abstract: Marine debris, especially plastic debris, is a global problem that requires intense monitoring and management since it affects humans, marine organisms and the environment. This study aimed to examine and compare the abundance and composition of marine macro debris found on three beaches of South Sulawesi Province, Indonesia. All three sites were situated in the Makassar Strait, and similarly exposed to the Indonesian Through-Flow; however each site had a different land-use designation: residential area (Labuange), recreational area (Lumpue), and restricted/private area (Bojo). From March to May 2018, marine macro debris was collected monthly on each beach, along a 2×25 m 2 transect (with three replicates/site). The samples were cleaned, sorted, counted, weighed, and analysed statistically. Plastic and rubber dominated marine macro debris in the study area (mean: 82-85%). The abundance of marine debris from Lumpue and Bojo beaches decreased drastically. However marine debris from Labuange beach remained greater in each sampling period (4.67-7.62 items per m 2 ), probably due to additional litter from the village. Beach morphology and wave direction pattern were also responsible for the high volume of marine debris washed up, especially on Labuange beach. Plastic and rubber, cloth/fabric, and processed lumber debris were the heaviest debris, with different orders in each site. Management efforts, including frequent local waste and marine debris collection, are required to minimize the impacts of marine debris on the environment.